Toxic effects of Lepidium sativum seed fixed oil on Wistar albino rats in acute and subacute toxicity models - Aragie, Teshome Gebremeskel; Asres, Kaleab; Ergete, Wondwossen; Woldekidan, Samual; Degu, Sileshi; Abebe, Abiy; Gemechu, Worku; Furgasa, Derso; Seyoum, Girma (Frontiers in Toxicology, 2025)
IntroductionL. sativum L. (family Brassicaceae) is a versatile herbal medicine in Ethiopia. The seed extract is widely employed in traditional medicine, whilst the seed oil is used as edible oil. However, there are no available studies conducted on the safety of the fixed oil of L. sativum seed in Ethiopia. Therefore, this study aimed to evaluate the acute and subacute toxicity of the oil in Wistar albino rats.MethodsAcute and subacute toxicity studies were conducted in Wistar albino rats. A single oral dose of L. sativum seed oil was administered, and the animals were followed for 14 days. The subacute oral dose toxicity study was conducted in rats of both sexes by repeated 28-day toxicity test as per OECD guidelines. Body weight was measured weekly, and observations of the animals were made regularly throughout the study period. Organ weight, histopathology, hematology, and clinical chemistry data were collected on the 29th day. One-way analysis of variance (ANOVA) was used to compare the means of the comparison groups and the results were presented as mean ± standard deviation, and significance was determined at the P-value of <0.05.ResultsIn this study, the LD50 of the fixed oil of L. sativum was found to be 2818.32 mg/kg. According to the World Health Organization, the oil is classified as slightly hazardous at a single oral dose administration. In the subacute toxicity study, rats treated with the oil showed significant changes behavioral indices such as piloerection, lethargy, and tremor. In addition, gross pathology of organs, body weight, biochemical, and hematological parameters were deranged.ConclusionThe results of the present study demonstrated that the fixed oil of L. sativum has toxic effects. Therefore, it is highly essential to create awareness among the Ethiopian public who use the seeds for medicinal purposes and/or consume the oil as edible oil about the possible health hazards that they may pose.